DIAGNOSTIC ACCURACY OF QUANTITATIVE WASHOUT CALCULATED ON TRIPHASIC CT SCAN FOR DIAGNOSIS OF HEPATOCELLULAR CARCINOMA KEEPING HISTOPATHOLOGY AS GOLD STANDARD: Quantitative Washout Calculated on Triphasic CT Scan - Hameed, Dr Huma; Nafees, Muhammad; Sameeuddin, Syed (Pakistan Armed Forces Medical Journal, 2018)
Objective: To determine the diagnostic accuracy of quantitative washout calculated on Triphasic CT scan fordiagnosis of hepatocellular carcinoma keeping histopathology as gold standard.Study Design: Descriptive, cross-sectional validation study.Place and Duration of Study: Armed Forces Institute of Radiology and Imaging Rawalpindi, from Feb 2016 toAug 2016.Material and Methods: A total of 132 patients of either sex with age in range 15-75 years diagnosed to have focalliver lesion on ultrasonography were included. Patients in whom focal lesion was cyst or abscess, patients withrenal failure, pregnancy or known sensitivity to contrast agents were excluded. All the patients then underwentTriphasic CT scan to calculate quantitative washout on delayed phase. The lesion was diagnosed as HCC ifpercent attenuation ratio was >107. The results were later correlated with histopathology findings.Results: Mean age was 49.75 ± 15.18 years. Out of 132 patients, 86 (65.15%) were males and 46 (34.85%) werefemales with ratio of 2:1. In Triphasic CT scan positive patients, 78 were True Positive and 09 were False Positive.Among 45, Triphasic CT scan negative patients, 07 were False Negative where as 38 were True Negative. Overallsensitivity, specificity, positive predictive value, negative predictive value and diagnostic accuracy of quantitativewashout calculated on Triphasic CT scan for diagnosis of hepatocellular carcinoma was 91.76%, 80.85%, 89.66%,84.44% and 87.88% respectively.Conclusion: This study concluded that quantitative washout calculated on Triphasic CT scan is a highly sensitiveand accurate non-invasive modality for diagnosis of hepatocellular carcinoma.